Managing ERP Projects Implementation: Multidimensional Analysis of Failure Causes - Anouar Ammi; Lalla Zhor Alaoui Omari; Jalal Azegagh (European Scientific Journal, ESJ, 2020)
Due to the persistence of failure to conduct information systems implementation projects, and because of the lack of researchers' consultation on the key factors of project management success, it is advisable to broaden the reflection on the main factors of failure and success, taking into account the contexts specific to each project. This paper lies within an exploratory approach, trying to identify the success factors of managing ERP implementation projects within companies, and proving the existence of strong interactions between the three project phases. It also tries to explain that project management should not be executed independently of the initial business plan. The methodological approach applied in this research is not part of a linear approach that investigates a phenomenon known in advance; it aims at building knowledge based on qualitative and empirical data. It is a combination of Maxwell's qualitative and empirical research' foundations, as well as the principles of grounded theory used in qualitative analyses in which the studied sample's size is not known in advance. The article showed that the success of ERP implementation is not as obvious, it should not be perceived separately from the study and exploitation's stages. In fact, it is the outcome of an appropriate preparation during the pre-project stage, optimized implementation during the project's conducting stage, as well as satisfaction of final users. This complexity requires the involvement of all stakeholders as well as agility at all levels. Thus, the stakeholders are required to take into account all events and possibilities that may affect the course of the software implementation project. At this level, defining a management approach and setting up a structure dedicated to that project becomes a must.